RESPON PESERTA DIDIK TERHADAP PENGGUNAAN APLIKASI CANVA DALAM PEMBELAJARAN MENULIS TEKS IKLAN DI MTs MIFTAHUL HUDA KIARAPAYUNG - Wiwin Winarti; Teti Sobari; Riana Dwi Lestari (IKIP Siliwangi, 2023)
This research is based on the observation that there are still many schools that ignore the use of learning media, especially when teaching students how to make advertisements. As a result, students are less enthusiastic and find it difficult to find ideas for making advertisements. Researchers suggest using the Canva application to overcome this problem. Students' responses to the use of the Canva application in making advertisements are the formulation of the problem in this study. This research uses the descriptive-qualitative method. The instrument used is a questionnaire. After the data on the results of student responses were analyzed, an average percentage of 89.5% was obtained, so it was categorized as very good. Based on this, it can be said that MTs Miftahul Huda Kiarapayung students enjoy using the Canva application program to write advertisements.